Alarming signs and symptoms in febrile children in primary care: an observational cohort study in The Netherlands. - Gijs Elshout; Yvette van Ierland; Arthur M Bohnen; Marcel de Wilde; Henriëtte A Moll; Rianne Oostenbrink; Marjolein Y Berger (PLoS ONE)
Context Febrile children in primary care have a low risk for serious infection. Although several alarming signs and symptoms are proposed to have predictive value for serious infections, most are based on research in secondary care. The frequency of alarming signs/symptoms has not been established in primary care; however, in this setting differences in occurrence may influence their predictive value for serious infections. Objective To determine the frequency of alarming signs/symptoms in febrile children in primary care. Design Observational cohort study. Clinical information was registered in a semi-structured way and manually recoded. Setting General practitioners' out-of-hours service. Subjects Face-to-face patient contacts concerning children (aged ≤16 years) with fever were eligible for inclusion. Main outcome measures Frequency of 18 alarming signs and symptoms as reported in the literature. Results A total of 10,476 patient contacts were included. The frequency of alarming signs/symptoms ranged from n = 1 (ABC instability; <0.1%) to n = 2,207 (vomiting & diarrhea; 21.1%). Of all children, 59.7% had one or more alarming signs and/or symptoms. Several alarming signs/symptoms were poorly registered with the frequency of missing information ranging from 1,347 contacts (temperature >40°C as reported by the parents; 12.9%) to 8,647 contacts (parental concern; 82.5%). Conclusion Although the prevalence of specific alarming signs/symptoms is low in primary care, ≥50% of children have one or more alarming signs/symptoms. There is a need to determine the predictive value of alarming signs/symptoms not only for serious infections in primary care, but as well for increased risk of a complicated course of the illness.